Validade, vigência e eficácia da norma jurídica do lançamento de ofício - Bernardi, Mariana Paludo Magarinos (2014)
The present study deals with the validity, currency and effectiveness of the legal rule of the Administrative Procedure Act. The Administrative Procedure Act, predicted in the article number 149 of the National Tax Code, is a definitive administrative act that introduces an individual and concrete rule in the legal system. According to the assumptions proposed by this study, the general and abstract legal rule of the Administrative Procedure Act is valid it legally exists by maintaining pertinent relations with the system; is current by having its own effect in accordance with time and space prescribed by the law; and finally is technically, legally and socially effective. The individual and concrete rule of the Administrative Procedure Act is valid in joining the legal system by means of the report in competent language the levy of the general and abstract rule (predicted in the article number 149 of the National Tax Code) in a concrete case; it is current and so is valid, because their concepts are coincident in time and space; at last, it has legally (declaratory and constitutive), technically and socially effectiveness